Scientific Rationality of Indigenous Plant Protection Practices on Banana (Musa spp.) Cultivation - A. Sakeer Husain and M. Sundaramari, (Indian Journal of Extension Education, 2018)
This study documented 75 Indigenous Plant Protection Practices (IPPPs) on banana cultivation in Kerala, India, out of which more practices were reported in the technology dimension of control of pseudostem weevil (29.33%), followed by management of bunchy top (26.67%) and control techniques of rhizome weevil (17.33%). Of the 75 IPPPs, 66.66 per cent belonged to pest management practices, while 33.34 per cent were related to disease management. Of the 19 practices that were selected for in-depth study, 78.95 per cent practices were found rational revealing the strong scientific base of these practices. The scientific rationale/operational principles of these practices elicited from scientists are also explained in this paper. The finding that only two practices (IPPPs-4 and 18) were known to and adopted by 50 per cent or more of the farmers, showed the poor knowledge and adoption levels of farmers regarding IPPPs in banana. The study highlights the significance of documenting and validating indigenous technical knowledge in agriculture, and effectively utilizing this traditional wisdom for enriching sustainable agricultural technologies.